Respiratory symptoms among industrial workers exposed to water aerosol. A pilot study of process water and air microbial quality - Bożena Krogulska; Renata Matuszewska; Marta Bartosik; Adam Krogulski; Maciej Szczotko; Dorota Maziarka (Nofer Institute of Occupational Medicine, 2013)
Background: The frequency of respiratory symptoms in workers exposed to water aerosol was evaluated along with the preliminary assessment of microbiological contamination of air and water used in glass processing plants. Material and Methods: A questionnaire survey was conducted in 131 workers from 9 glass processing plants. Questions focused on working conditions, respiratory symptoms and smoking habits. A pilot study of air and water microbiological contamination in one glass processing plant was performed. Water samples were tested for Legionella in accordance with EN ISO 11731-2:2008 and for total colony count according to PN-EN ISO 6222:2004. Air samples were tested for total numbers of molds and mildews. Results: During the year preceding the survey acute respiratory symptoms occurred in 28.2% of participants, while chronic symptoms were reported by 29% of respondents. Increased risks of cough and acute symptoms suggestive of pneumonia were found among the respondents working at a distance up to 20 m from the source of water aerosol compared to other workers (OR = 2.7), with no difference in the frequency of other symptoms. A microbiological analysis of water samples from selected glass plant revealed the presence of L. pneumophila, exceeding 1000 cfu/100 ml. The number of bacteria and fungi detected in air samples (above 1000 cfu/m3) suggested that water aerosol at workplaces can be one of the sources of the air microbial contamination. Conclusions: The questionnaire survey revealed an increased risk of cough and acute symptoms suggestive of pneumonia in the group working at a shortest distance form the source of water aerosol. Med Pr 2013;64(1):47-55